2019
DOI: 10.11648/j.ajpn.20190701.13
|View full text |Cite
|
Sign up to set email alerts
|

Community Services, Progression Rate, and Nursing Home Placement In Persons with Alzheimer’s Disease

Abstract: There are many factors influencing when a person with Alzheimer's disease (AD) or another dementia is placed in a nursing home (NHP). The aims of this study were to determine if introducing home and community-based services (HCBS) at different stages of disease severity influenced time to NHP in a sample of persons living with AD (n = 1210); examine if disease pre-progression rate (PPR) influenced time to NHP; and explore the interaction between disease severity at first use of HCBS and PPR on time to NHP. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Additionally, it has been suggested that caregiver burden may impact mortality rates in persons with dementia [ 12 ], although the reasons are not clear. Preliminary evidence suggests that the caregivers of persons with dementia who do not receive community-based social support (i.e., homemaker and home health services) may experience greater burden, making time to placement in long-term care settings such as nursing homes sooner than the caregivers who receive this support [ 13 ]. Some research suggests that there are higher mortality rates among persons with dementia the first year they are placed in a long-term care setting as compared to living in their own home [ 14 , 15 ].…”
Section: Caregiver Stress and Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been suggested that caregiver burden may impact mortality rates in persons with dementia [ 12 ], although the reasons are not clear. Preliminary evidence suggests that the caregivers of persons with dementia who do not receive community-based social support (i.e., homemaker and home health services) may experience greater burden, making time to placement in long-term care settings such as nursing homes sooner than the caregivers who receive this support [ 13 ]. Some research suggests that there are higher mortality rates among persons with dementia the first year they are placed in a long-term care setting as compared to living in their own home [ 14 , 15 ].…”
Section: Caregiver Stress and Burdenmentioning
confidence: 99%
“…Geriatrics 2024, 9, 38 2 of 13 Burden among family caregivers has been associated with physical (e.g., sleep difficulties, cardiovascular disease, reduced immune response, etc. ), emotional (e.g., mental health difficulties), social and lifestyle changes (e.g., relationship challenges, lower social engagement) [5,6], and spiritual struggles [7,8].…”
Section: Caregiver Stress and Burdenmentioning
confidence: 99%